Save the Planet, UAV Raw Imagery in Wild/Desert for Waste Detection - Abderrahmane Maaradji (22586726) (2025)
This dataset contains 2088 raw, geotagged RGB images captured with a DJI Mavic 2 Pro to support computer vision research on waste detection in a desert-like field (please refer to the Readme file for details).